Peripheral Blood NRF2 Expression as a Biomarker in Human Health and Disease - Lee E. Neilson; Joseph F. Quinn; Nora E. Gray (MDPI AG, 2020)
Nuclear factor erythroid 2-related factor 2 (NRF2), a transcription factor which plays a critical role in maintenance of cellular redox, has been identified as a therapeutic target in a number of human diseases. Several reports have demonstrated beneficial effects of NRF2 manipulation in animal models of disease, and one NRF2-activating drug, dimethyl fumarate, is already approved for the treatment of multiple sclerosis. However, drug discovery is slowed due to a dearth of biomarkers which can inform target engagement and magnitude and duration of action. Peripheral blood mononuclear cells (PBMCs) are an accessible, minimally-invasive source of biomarkers which can be readily assayed and objectively monitored as a surrogate endpoint of NRF2 activation in clinical trials. We undertook a review of the literature on PBMC NRF2 measurements in human studies to explore its role as a suitable biomarker in various contexts of health and disease. It is clear that NRF2 and its target genes can be readily assayed from PBMCs in multiple disease contexts and may track with disease progression. Further work needs to be undertaken to evaluate its stability but should be considered as an exploratory marker in clinical trials targeting NRF2 activation.